Development cooperation at a tipping point: How, why and through what mechanisms do policy norms break? - Andrew Sumner; Stephan Klingebiel (German Institute of Development and Sustainability (IDOS), 2025)
This paper applies the concepts and theories of "policy norms" to the disruptive effects of the second Trump administration on global development cooperation. We argue that recent US actions represent more than a domestic political shift. They signal a tipping point to longstanding norms of the development cooperation system and specifically multilateralism as well as notions of global solidarity. This paper's objective is to explain how, why and through which political and institutional mechanisms policy norms break down or are reconstituted in global development cooperation. It uses the current moment as a case study of "norm antipreneurship", potentially even "norm imperialism" illustrating the political and institutional strategies through which policy norms are currently been contested, dismantled or displaced. This paper addresses a set of questions: (i) What are the core mechanisms through which development cooperation norms are formed, contested and fragmented? (ii) How is the second Trump administration seeking to reshape normative regimes in development cooperation? (iii) What research agenda is needed to understand norm change in a multipolar and contested development cooperation landscape?
Keywords: 320; development cooperation; norm contestation; policy norms; global (dis)order; nationalist conditionality regime; New Washington Dissensus